Addressing Food Crises and Leveraging the "Hidden Middle" - Vos, Rob (2020)
Rob Vos SEMINAR Virtual Event --Discussion of the 2020 Global Food Policy Report Co-Organized by the Ministry of Foreign Affairs, Government of the Netherlands, IFPRI, and Food & Business Knowledge Platform APR 28, 2020 - 10:00 AM TO 11:15 AM EDT